Effect of extraction temperature of taro mucilage on physicochemical and rheological properties - Arici, Muhammet; Senol, Burcu Mine; Ozturk, Eylul; Ozmen, Duygu; Toker, Omer Said (SPRINGER, 2024)
Mucilage, which is the main component of the taro plant, and is known to have significant health benefits, has become a versatile ingredient in the food industry due to its richness in fiber and protein and its unique rheological properties. Taro mucilage has a rich content of various bioactive chemicals such as saponins, tannins, flavonoids, and phenolic acids along with being viscous and water-soluble. The effective use of taro mucilage is only possible if it is efficiently extracted, which has created a pre-treatment or additional treatment requirement. Temperature application plays a crucial role in taro mucilage extraction and significantly affects its composition, yield, and quality. This present study focuses on the effects of different temperatures (20, 40, 60 and 80 C-degrees) applied during taro mucilage extraction on physicochemical and rheological properties. The water-holding capacity of taro mucilage samples decreased significantly (p < 0.05) from 0.48 to 0.12% with a rise in temperature while there is no significant linear decrease or increase in oil-holding capacity and solubility values. Emulsifying activity and emulsion stability parameters significantly improved by increasing temperature (p < 0.05). The zeta potential ranged from - 10.49 to - 24.09 so stable emulsions were formed. At higher temperatures, lighter mucilage was obtained for both the powder and aqueous form of mucilage. The samples showed pseudoplastic behavior and the temperature increased the K value up to 60(degrees)C.
Keywords: Colocasia esculenta; Taro; Mucilage; Rheology; SEED MUCILAGE; FUNCTIONAL-PROPERTIES; OPTIMIZATION; GUM; Food Science & Technology